Pendampingan Pada Ibu Menyusui Mempengaruhi Keberhasilan Praktek Pemberian ASI pada Masa Adaptasi Kebiasaan Baru Pandemi COVID-19 - Ni Made Rai Widiastuti; Kadek Widiantari (Politeknik Kesehatan Kartini Bali, 2022)
Breastfeeding assistance in supporting breastfeeding can help increase the knowledge, motivation and behavior of mothers in giving breast milk to babies. The purpose of the study was to identify the effect of breastfeeding assistance on the success of mother's knowledge, motivation and behavior in breastfeeding. The research design was a quasi-experimental with pre and post-test non-equivalent control group design. The sampling technique was accidental sampling which consisted of 30 respondents from the intervention group and 30 respondents from the control group. Data analysis used descriptive analysis and analysis used different tests. The results showed that the respondents who received the intervention there was an increase in the knowledge score of 2,514 with a value of t = 6,970, an increase in the motivation score of 2,353 with a value of t = 13,179, and an increase in the score of 1.324 with a value of t = 8,043. From the results of this study, it is expected that health workers can provide breastfeeding assistance to breastfeeding mothers in supporting the success of breastfeeding by providing exclusive breastfeeding.